2018
DOI: 10.1016/j.isci.2018.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Facilitates Biomethane Production from Protein-Derived Glycine in Anaerobic Digestion

Abstract: SummaryInterspecies electron transfer is a fundamental factor determining the efficiency of anaerobic digestion (AD), which involves syntrophy between fermentative bacteria and methanogens. Direct interspecies electron transfer (DIET) induced by conductive materials can optimize this process offering a significant improvement over indirect electron transfer. Herein, conductive graphene was applied in the AD of protein-derived glycine to establish DIET. The electron-producing reaction via DIET is thermodynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…At high nZVI concentrations (5 g⋅L –1 ), other potential n-butyrate producers such as Oscillibacter , unclassified Oscillospiraceae and Sedimentibacter species were enriched. These taxa have also been enriched in bioelectrochemical systems ( Breitenstein et al, 2002 ; Lin et al, 2018 ; Dessì et al, 2021 ) and Oscillibacter species in ethanol-based chain elongation with nZVI ( Fu et al, 2020 ; Wang et al, 2020 ). However, nZVI caused higher pH conditions and directed the conversion of residual lactate toward propionate formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At high nZVI concentrations (5 g⋅L –1 ), other potential n-butyrate producers such as Oscillibacter , unclassified Oscillospiraceae and Sedimentibacter species were enriched. These taxa have also been enriched in bioelectrochemical systems ( Breitenstein et al, 2002 ; Lin et al, 2018 ; Dessì et al, 2021 ) and Oscillibacter species in ethanol-based chain elongation with nZVI ( Fu et al, 2020 ; Wang et al, 2020 ). However, nZVI caused higher pH conditions and directed the conversion of residual lactate toward propionate formation.…”
Section: Discussionmentioning
confidence: 99%
“…Some strains, however, possess putative proteins involved in lactate metabolism (section “Lactate Metabolism and Racemization”). Sedimentibacter species have been suggested to be electroactive as they were enriched in bioelectrochemical systems ( Vilajeliu-Pons et al, 2016 ) and graphene-amended anaerobic digestion ( Lin et al, 2018 ). Additionally, some species are involved in extracellular electron transfer for Fe 3+ reduction ( Burkhardt et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increase of Bacteroides, which secrete hydrolyzing enzymes such as cellulases, amylases, proteases and lipases, and play an important role in the acidogenesis phase, could serve as warning signal to impending reactor inhibition (Martin Vincent et al, 2018). Sedimentibacter species are able to ferment glycine to acetic acid without H 2 gas production (Lin et al, 2018). Lachinospiraceae and Ruminococcus with the capability of degrading complex vegetable materials to short-chain fatty acids, specifically acetate, propionate, and butyrate (Cardinali-Rezende et al, 2016) were reported to appear simultaneously with Mogibacteriaceae in anaerobic digesters (da Silva Martins et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In the MES-AD system for biogas upgrading, CH 4 is generated bioelectrochemically mainly via two possible mechanisms: direct electron transfer (DET) from the cathode to electroactive microbes (Equation 2 iScience Review (Equation 3), which has a higher energy barrier (E cat = À0.421 V vs. SHE) but is often the main route (Gildemyn et al, 2017). Since the standard potential of the DET reaction is much higher than that of IDET hydrogen production, researchers are seeking ways to improve the energy-efficient process of DET biogas enrichment (Lin et al, 2017(Lin et al, , 2018a(Lin et al, , 2018bZhao et al, 2020). Recently Salimijazi et al developed a theoretical calculation method on the electricity-microbes-biofuel conversion efficiency and predicted that the efficiency of engineered in vivo CO 2 fixation can increase from ca.…”
Section: Microbial Electrosynthesismentioning
confidence: 99%
“…In the MES-AD system for biogas upgrading, CH 4 is generated bioelectrochemically mainly via two possible mechanisms: direct electron transfer (DET) from the cathode to electroactive microbes ( Equation 2 ), which has a lower energy barrier (E cat = −0.244 V vs. standard hydrogen electrode (SHE)); or indirect electron transfer (IDET) by intermediate diffusion of H 2 production ( Equation 3 ), which has a higher energy barrier (E cat = −0.421 V vs. SHE) but is often the main route ( Gildemyn et al., 2017 ). Since the standard potential of the DET reaction is much higher than that of IDET hydrogen production, researchers are seeking ways to improve the energy-efficient process of DET biogas enrichment ( Lin et al., 2017 , 2018a , 2018b ; Zhao et al., 2020 ). Recently Salimijazi et al.…”
Section: Emerging Biomethane Production Technologiesmentioning
confidence: 99%